Currency crises in Turkey: An empirical assessment - ARI, ALİ (ELSEVIER SCIENCE BV, 2018)
Contrary to many previous empirical studies on currency crises, this paper aims to test the relevance of different methodologies and crisis definitions in estimating crisis determinants and predicting crisis episodes in the case of Turkey over the period of 1990-2014. Empirical results first show that the inflation rate, portfolio investments, and the ratio of bank foreign deposits to total deposits are found to be the leading determinants of Turkish currency crises in different model estimations. Secondly, empirical findings clearly indicate the superiority of the Markov approach in predicting crisis episodes in Turkey when compared to the logit model.
Keywords: Currency crises; Early warning system; Logit; Markov-switching; Turkey; EARLY WARNING SYSTEMS; FINANCIAL CRISES; EMERGING MARKETS; INDICATORS; PREDICT; BALANCE